DIGITAL TRANSFORMATION OF HOUSING AND COMMUNAL HOUSEHOLD IN RUSSIA - O. Demenko; A. Tikhomirov (Вестник университета)
The transition of the Russian economy to the electronic exchange of data in the sphere of housing and communal household is described. The influence of the system of public administration, namely the program «Digital Economy of the Russian Federation». This program has been designed to introduce electronic data interchange for the sphere of housing and communal household since the automation of data collection of utility meters and utility payments is able not only to save considerable amounts of budget, but also to provide reliable impartial accounting of consumption of communal resources. The development of the life of the population has been predicted with the continuing urbanization of society. The strengths and weaknesses of urban infrastructure development are revealed. The aspects of introduction of the digital management model are presented as the only affordable and economically justified way of building the housing and communal household in the future.